International economic polarity between the two blocs (China and the United States): A future vision (قضايا سياسية, 2024)
The Belt and Road Initiative adopted by China is an effective strategy to get rid of the problems and crises plaguing China in its internal and external surroundings and areas of influence, especially the Indo-Pacific region, the Middle East, Central Asia, Africa and the Horn of Africa, and to impose certain policies that China seeks through the initiative to take an international position in The international system, and linking the world's economies to its economy by making its currency (the yuan) a global trading currency different from the US dollar, by establishing financial institutions that primarily serve its interests. Beijing also seeks to secure energy corridors and seize the sources of its exports to tighten its control over the economy in general, and as a result, increase its power Military and expanding its bases in countries and regions of the world.